2007
DOI: 10.1042/bst0350318
|View full text |Cite
|
Sign up to set email alerts
|

Unusual aspects of the polyamine transport system affect the design of strategies for use of polyamine analogues in chemotherapy

Abstract: One strategy for inhibiting tumour cell growth is the use of polyamine mimetics to depress endogenous polyamine levels and, ideally, obstruct critical polyamine-requiring reactions. Such polyamine analogues make very unusual drugs, in that extremely high intracellular concentrations are required for growth inhibition or cytotoxicity. Cells exposed to even sub-micromolar concentrations of such analogues can achieve effective intracellular levels because these compounds are incorporated by the very aggressive po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Studies show that polyamine metabolism is dysregulated in many types of cancer, leading to polyamine levels significantly higher than in normal tissues (7,8). It was also suggested that the polyamine pathway is a distal downstream target for a number of validated oncogenes and that inhibition of polyamine synthesis disrupts the action of those genes (1,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that polyamine metabolism is dysregulated in many types of cancer, leading to polyamine levels significantly higher than in normal tissues (7,8). It was also suggested that the polyamine pathway is a distal downstream target for a number of validated oncogenes and that inhibition of polyamine synthesis disrupts the action of those genes (1,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…It also has been previously stated that polyamine analogues such as BENSpm can actually limit their own uptake by their ability to induce antizyme and so downregulate additional polyamine uptake (Mitchell et al 2007b). In this case, the loss of AZ1 results in loss of uptake regulation, resulting in increased BENSpm uptake, accumulation, and subsequent toxicity in AZKD cells compared to SCR clones.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are expected to be somewhat transitory, however, since increased polyamine uptake will induce expression of antizyme, which will inhibit polyamine transport. The ratio of AZ:AZI within the cell will determine the precise effect on polyamine transport following an increase in AZI levels (60). Numerous experiments thus far have shown that constitutive overexpression of AZI results in increased polyamine uptake and increased accumulation of polyamine analogs (36, 61).…”
Section: Reviewmentioning
confidence: 99%